Influence of the plough with tekrone mouldboards and landsides on ploughing parameters - Nadykto, Volodymyr; Надикто, Володимир Трохимович; Надыкто, Владимир Трофимович; Kiurchev, Volodymyr; Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Findura, P.; Karaiev, Oleksandr; Караєв, Олександр Гнатович; et al. (My University, 2020)
This paper is dedicated to Tekrone composite material utilization in agricultural machinery. In terms of its technical properties, tekrone is very similar to steel 60 that is used for production of plough mouldboards and landsides. However, Tekrone shows more preferable characteristics, because its friction coeffi cient (kf) is 2.6 times lower in contrast to steel 60. This fact indicates that the draft resistance can be decreased by replacing the plough mouldboards and landsides made of steel 60 with their counterparts made of Tekrone. This science hypothesis was confi rmed by experimental investigation results. Analyses showed that utilization of plough with Tekrone mouldboards and landsides instead of steel ones signifi cantly reduces their sticking to the wet soil. This results in a “soil moves over plough mouldboard surface” process instead of a “soil moves over soil” process. The plough draft resistance was decreased by 13.6% after replacement of the steel equipment with Tekrone one. Simultaneously, the performance of new tractor-plough aggregate was increased by 12.6%, the specifi c fuel consumption was reduced by 11.8%, and the preserving probability of the agrotechnological ploughing depth tolerance (±2 cm) was increased from 88% to 93%.
Keywords: ploughing; friction coefficient; draft resistance; soil sticking